Efficacy evaluation of contrast-enhanced magnetic resonance imaging in differentiating glioma from metastatic tumor of the brain and exploration of its association with patients’ neurological function - Shi, Zhuo; Jiang, Jiuming; Xie, Lizhi; Zhao, Xinming (Frontiers in Behavioral Neuroscience, 2022)
Objective: To determine the efficacy of contrast-enhanced MRI in differentiating gliomas (GL) from metastatic tumor of the brain (MTB) and its association with patients’ neurological function. Methods: Admitted between April 2019 and January 2022, 49 patients with pathologically confirmed GL and 42 cases with MTB were selected as the subjects for retrospective analysis. All patients were examined by a set of MRI sequences that included T1WI, T2WI, FLAIR, and DWI. The values of fractional anisotropy (FA), apparent diffusion coefficient (ADC) and operation coefficient (Ktrans) were calculated by taking the tumor parenchyma area, cystic area and peritumor edema area as the regions of interest (ROIs). And according to the Mini-mental State Examination (MMSE) results, the contrast-enhanced MRI with patients’ neurological dysfunction was observed. Results: The clinical symptoms and MRI findings of MTB and GL were basically the same, mainly showing neurological symptoms. The tumor parenchyma area and cystic area were mainly located in the tumor periphery and tumor central area, respectively, while the peritumor edema area was widely distributed, showing an irregular patchy edema zone. Contrast-enhanced scans suggested obvious enhancement in the tumor parenchymal area, presenting with nodular and annular enhancement, but no enhancement in the tumor cystic and peritumor edema areas. There was no difference between GL and MTB in FA values of tumor cystic area and peritumor edema area (P>0.05), but the FA value of the parenchyma area of GL was higher (P<0.05). Besides, GL and MTB showed no difference in ADC and Ktrans values (P>0.05), while the former presented lower ADC values and higher Ktrans values of the peritumor edema area than the latter (P<0.05). In GL and MTB patients, the FA and Ktrans values of all ROIs in those with neurological dysfunction were higher compared with those without neurological dysfunction, while the ADC values were lower (P<0.05). Conclusion: Contrast-enhanced MRI of peritumor edema area can effectively distinguish GL from MTB, and improve the accuracy of early clinical screening, thus providing more reliable life security for patients.